ECONOMIC POLICY TO OVERCOME STAGNATION AFTER THE FINANCIAL CRISIS - V. D. Kuligin (Вестник университета)
The article considers the downward spiral of deflation, its causes and consequences. The paper discusses the compression of aggregate demand and the subsequent recession. The study discloses the content of the liquidity trap created by the behavior of borrowers. The author traces the connection between the events of the “lost decades” in Japan and the stagnation of production in leading Western countries after the global financial crisis. In both cases, the large-scale use of fiscal and monetary incentives did not cause a sharp rise in business activity. The paper concludes that the operation of the market mechanism is blocked by budget and monetary policies. Obstacles to entrepreneurial activity and energy lead to the loss of necessary information generated by market agents. This circumstance prolongs the stagnation of the economy.